A controlled study of emotional dysfunction in adult women with ADHD - Ortal Slobodin; Michal Har Sinay; Ada H. Zohar (PLoS ONE, 2025)
Objective Given the increased socio-emotional burden of ADHD symptoms in women, the current study examined the associations between ADHD symptoms, emotional dysregulation, and executive function deficits. We also examined two types of executive function deficits, working memory and task shifting, as potential mediators of the link between women’s ADHD symptoms and emotional dysregulation. Method The study included 176 women between 20 and 30 years of age. Of these, 82 reported a known diagnosis of ADHD, and 94 reported no known diagnosis. Participants completed questionnaires addressing the severity of ADHD symptoms, executive function deficits, emotional dysregulation, alexithymia, positive affect, and negative affect. Results Emotional dysregulation was associated with ADHD symptom severity and executive function deficits. Women with ADHD showed more frequent use of non-adaptive emotion regulation strategies, including negative affect and alexithymia, compared to women without ADHD symptoms. In addition, results showed that executive function deficits (in working memory and task shifting) mediated the relationship between ADHD symptoms and emotional dysregulation. Conclusions These findings add further support to the growing body of research suggesting that not only inattention, hyperactivity, and impulsivity, but also emotional dysregulation are core components of ADHD. Shifting clinical attention to emotional dysregulation symptoms may improve the diagnosis and treatment of women’s ADHD.